Effectiveness of Implementing Mobile Monitoring Applications on Compliance of Diabetes Mellitus Patients in The Infectious Ward of Mekar Sari Hospital - Achmad Fauzi; Kanith Hanifa Hawa Adamiya (Universitas Malahayati Lampung, 2026)
ABSTRACT Diabetes Mellitus (DM) is a chronic metabolic disease with many causes which is generally characterized by increased blood glucose levels accompanied by impaired carbohydrate, lipid, and protein metabolism as a result of impaired insulin function. In the current era, technology can facilitate health care with simple messages and warnings that help achieve adherence to treatment for patients with the disease . Lack of knowledge, lack of family support, poor communication with health workers, and limited health literacy are factors that hinder the compliance of diabetes mellitus sufferers in taking medication, thus causing blood sugar to tend to be uncontrolled.To determine the effectiveness of the application of mobile monitoring applications on dietary compliance of Diabetes Mellitus patients in the Inpatient Room of Mekar Sari Hospital, Bekasi. This research uses a quantitative design with a quasi-inquiry method. experiment one group pre-test and post-test . The research sample consisted of 24 patients in the inpatient ward of Mekarsari Hospital, Bekasi . Data analysis was performed using the Dependent T- test or Wilcoxon test , according to the data distribution. The results of the study showed that the use of mobile monitoring accompanied by filling out a diet questionnaire had a significant impact on the management of Diabetes Mellitus patients. This was demonstrated by the results of the statistical analysis with a p-value of 0.000 (0.05 ) , which indicates a significant relationship between the use of mobile monitoring and patient compliance in filling out the diet questionnaire.The use of mobile monitoring is accompanied with filling proven diet questionnaire give significant influence in management Diabetes Mellitus patients . This shown by the results analysis statistics showing existence meaningful relationships between mobile monitoring usage and level compliance patient in fill in diet questionnaire . With Thus , the application of mobile monitoring can become one of the effective strategies For increase compliance patient as well as support more optimal management of Diabetes Mellitus . Keywords: Diabetes Mellitus , Effectiveness , Mobile Monitoring.